2015
DOI: 10.1161/circinterventions.114.001816
|View full text |Cite
|
Sign up to set email alerts
|

Distal Embolization of Hydrophilic-Coating Material From Coronary Guidewires After Percutaneous Coronary Interventions

Abstract: Background— Coronary guidewires are indispensable during percutaneous coronary interventions. Nowadays, most guidewires have hydrophilic coatings to improve their trackability, allowing easy lesion passage and facilitating balloon and stent positioning. Recent reports, however, have raised concerns about detachment and subsequent embolization of these hydrophilic coatings. Methods and Results— We have retrospectively reviewed the histological samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 13 publications
(16 reference statements)
3
55
2
Order By: Relevance
“…A recent analysis of material captured through use of an embolic protection device during mitral valve repair showed that polymer embolism occurred as frequently as acute thromboembolism (86%), with native tissue emboli (64%) and organizing thrombi (29%) noted less often 18 . Frequent polymer coating emboli have also been affiliated with other percutaneous procedures 19,20 . Thus, polymer embolism should be included in the differential of unanticipated ischemic or inflammatory complications as well as unexplained vasculopathies occurring during the post-procedural clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of material captured through use of an embolic protection device during mitral valve repair showed that polymer embolism occurred as frequently as acute thromboembolism (86%), with native tissue emboli (64%) and organizing thrombi (29%) noted less often 18 . Frequent polymer coating emboli have also been affiliated with other percutaneous procedures 19,20 . Thus, polymer embolism should be included in the differential of unanticipated ischemic or inflammatory complications as well as unexplained vasculopathies occurring during the post-procedural clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Grundeken et al[11] examined the possibility of distal polymer embolization in two ways - they examined the aspirate from patients undergoing aspiration thrombectomy and reported that 45% samples had polymer material in them. Also, examination of autopsy specimens from patients who had undergone PCI showed intramyocardial polymer in 10% subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Given the retrospective design, this finding should be treated as hypothesis generating and hopefully will trigger prospective analysis to confirm or refute this association. The etiology for this risk is believed to be polymer shearing and micro-embolization which has been proven by multiple small but rigorously conducted studies[11,13]. We believe that much has to be learned about the potential role of polymer shearing and embolization in myonecrosis post CBL intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the widespread use of these procedures, certain complications are becoming more evident, including acute granulomatous inflammatory response to the hydrophilic polymer which often coats the devices used to perform these procedures. This phenomenon has been observed following endovascular interventions in the anterior and posterior cerebral circulation [613], pulmonary thrombectomy [1416], cardiac catheterization [1720], vascular catheterization with kidney involvement and acute renal failure [21,22], as well as polymer embolization to the skin [2325] and meninges [26]. This is often an acute response after catheter intervention.…”
Section: Introductionmentioning
confidence: 99%